The platform of spoof videos: The case of Tudou.com - Li, Siling (2012)
This paper analyses the enabling and constraining role of platforms in the development of online video-spoofing culture in China. Using Tudou.com, one of China’s most popular video-sharing sites, as a case study, the paper discusses how video-sharing sites facilitate and curtail the self, and how they negotiate and balance among users, clients and the state, teasing out the complex politics of platforms in China. Particular reference is made to three “star users”, Jiaoshou, Hu Ge and Corndog, who gained fame for themselves via the popularity of their spoof videos on this platform.